2006
DOI: 10.1074/jbc.m513336200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin I Protects Podocytes from Apoptosis

Abstract: The limited regenerative capacity of the glomerular podocyte following injury underlies the development of glomerulosclerosis and progressive renal failure in a diverse range of kidney diseases. We discovered that, in the kidney, cyclin I is uniquely expressed in the glomerular podocyte, and have constructed cyclin I knock-out mice to explore the biological function of cyclin I in these cells. Cyclin I knock-out (؊/؊) podocytes showed an increased susceptibility to apoptosis both in vitro and in vivo. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 46 publications
2
74
0
Order By: Relevance
“…8 In contrast to other cyclins its mRNA levels do not fluctuate during the cell cycle. [5][6][7] Moreover, we showed that Cyclin I null mice are normal, consistent with the notion that Cyclin I is not required for cell differentiation. The Cyclin I null mouse, and subsequent cell culture studies using cells isolated from these mice such as fibroblasts and podocytes, showed that in contrast to other cyclins, Cyclin I has no role in regulating cell proliferation.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…8 In contrast to other cyclins its mRNA levels do not fluctuate during the cell cycle. [5][6][7] Moreover, we showed that Cyclin I null mice are normal, consistent with the notion that Cyclin I is not required for cell differentiation. The Cyclin I null mouse, and subsequent cell culture studies using cells isolated from these mice such as fibroblasts and podocytes, showed that in contrast to other cyclins, Cyclin I has no role in regulating cell proliferation.…”
supporting
confidence: 72%
“…This paradigm has since been altered by the discovery of atypical cyclin proteins and dependent kinases including cyclin C-Cdk8, 1 cyclin H-Cdk7, 2 cyclin K-Cdk9, 3 cyclin T-Cdk9, 4 or Cyclin I. [5][6][7] Cyclin I, first cloned from human forebrain cortex, shows highest sequence homology to cyclins G 1 and G 2 . 8 In contrast to other cyclins its mRNA levels do not fluctuate during the cell cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These mRNAs included those that encode the prosurvival proteins Akt1 and cyclin I. 13,56,57 Akt is one of the most active kinases in cancer cells, while the anti-apoptotic protein cyclin I is highly expressed in breast cancer and its increased level in serum is associated with pancreatic cancer. 56,58,59 Nucleolin and microRNA processing.…”
Section: Nucleolin Target Transcriptsmentioning
confidence: 99%
“…The G-type cyclins (cyclin G1, G2, and I) on the other hand are associated with cell-cycle arrest (15). Cyclin G1 is involved in G 2 -M phase arrest, whereas cyclin I is thought to play a role in apoptosis (16). Cyclin G2 (CCNG2) has been shown to inhibit cell-cycle progression by preventing G 1 to S-phase transition (14,15,17).…”
Section: Introductionmentioning
confidence: 99%